2020
DOI: 10.1186/s12889-019-8139-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reducing the posted speed limit to 30 km per hour on pedestrian motor vehicle collisions in Toronto, Canada - a quasi experimental, pre-post study

Abstract: Background: Pedestrian related deaths have recently been on the rise in Canada. The effect of changing posted speeds on the frequency and severity of pedestrian motor vehicle collisions (PMVC) is not well studied using controlled quasi-experimental designs. The objective of this study was to examine the effect of lowering speed limits from 40 km/h to 30 km/h on PMVC on local roads in Toronto, Canada. Methods: A 30 km/h speed limit on local roads in Toronto was implemented between January 2015 and December 2016… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Despite having stricter road traffic laws, there has been negligible improvement in road safety (Mphela, 2011). While the reduction of posted speeds has led to improvements on pedestrian safety in other countries as reported by Fridman et al (2020) and Marshall (2012), driver non-compliance remains a threat in Botswana. Improving law enforcement and nurturing driver compliance is ideal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite having stricter road traffic laws, there has been negligible improvement in road safety (Mphela, 2011). While the reduction of posted speeds has led to improvements on pedestrian safety in other countries as reported by Fridman et al (2020) and Marshall (2012), driver non-compliance remains a threat in Botswana. Improving law enforcement and nurturing driver compliance is ideal.…”
Section: Discussionmentioning
confidence: 99%
“…In areas where the road safety awareness messages were combined with engineering interventions (redesigning of pedestrian access roads), pedestrian collisions declined by as much as 79%. In Toronto, Canada a quasi-experimental study by Fridman et al (2020), where a posted speed limit was reduced from 40 to 30km/h, led to a 28% decrease in pedestrian road accidents compared to roads that were left at 40 km/h. However, Matsui and Oikawa (2019) found that pedestrian collisions that happen at low speeds tend to be more fatal than those happening at high speeds at signalized intersections during daytime.…”
Section: Literature Reviewmentioning
confidence: 99%
“…36 Lowering the speed limits from 40 to 30 km/hour has been associated with a 29% decrease in child pedestrian motor vehicle collisions in Toronto. 27 ASE has been found to substantially reduce speeding, speed violations, collisions, injuries and deaths around schools. 37 38 Physical infrastructure changes related to traffic calming are important around schools, as this study found more than half of schools did not have any traffic calming measures at their frontages.…”
Section: Original Researchmentioning
confidence: 99%
“…If we focus on the effects of speed reduction on pedestrian fatality risk we see that they are treated in many studies (De Pauw et al, 2014;De Pelsmacker and Janssens, 2007;Elvik, 2009;Fridman, 2020;Heydari et al al., 2014;Hussain et al, 2019;Rosén, 2009). A reduction in speed limits can help reduce the kinetic energy of the vehicle and therefore, the damage to the pedestrian.…”
Section: 𝑃 𝑉 𝐴mentioning
confidence: 99%